PTH-141 Pattern of single lymph node metastasis in carcinoma of the oesophagus. (22nd June 2015) - Navidi, M; Lagarde, S; Wahed, S; Phillips, A; Immanuel, A; Hayes, N; Griffin, M
Abstract : Introduction: The presence of lymphatic dissemination in oesophageal cancer affects prognosis. The relevance of location of an involved solitary lymph node is unclear. The concept of sentinel node guided lymphadenectomy to reduce surgical stress of a transthoracic operation has some advocates. However, the site of solitary lymph node metastasis, is unpredictable. Similarly, metastases to anatomically distant lymph nodes, known as skip lesions, could develop in the early phase of lymphatic invasion. The aim of this study was to examine the pattern of a single named lymph node metastasis in patients with oesophageal adenocarcinoma (AC) or squamous cell carcinoma (SCC) who underwent resection with curative intent. No study to date has investigated this concept. Method: Results of consecutive patients from a prospectively maintained database were analysed. All patients with potentially curable AC or SCC who underwent a radical two-field, two-stage, transthoracic oesophagectomy were included. Ex-vivo surgical dissection of the specimen was carried out post-operatively by the surgeon, with harvested lymph node stations labelled. This permitted accurate 'lymph node mapping'. All harvested lymph nodes were examined by a consultant histopathologist. Results: Between 1995 and 2014 a total of 120 patients with one positive lymph node who had undergone a radical two-field, two-stage oesophagectomy were identified. A median age of 65 (45–80) was observed. Seventy three ACs and 47 SCCs were noted. Twenty three middle oesophageal (19.2%), 54 lower oesophageal (45%) and 43 (35.8%) junctional tumours were resected. There was no difference between patterns of solitary lymphatic metastases between AC and SCC. The pattern and number of solitary lymph node metastasis is as follows: paracardial 34 (28.3%); paraoesophageal 31 (25.8%); left gastric 28 (23.3%); subcarinal/bronchial 10 (8.3%) and truncal/coeliac/splenic 9 (7.5%). Tumour location and corresponding single node metastasis are summarised in Table 1 . Median survival for patients with AD and SCC were similar at 45 months and 52 months respectively (p = 0.84). Conclusion: This study provides further support to the concept that metastasis to anatomically distant lymph nodes (skip metastasis), could develop even in the early phase of lymphatic invasion in oesophageal carcinoma. This unpredictability necessitates a radical resection. This can only be achieved with an extended transthoracic operation to allow a complete two-field lymphadenectomy in order to provide locoregional clearance and a potentially curative resection. Disclosure of interest: None Declared.